Diffusion-Weighted MR Imaging - Koh, D. M.; Thoeny, H. C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The clinical applications of diffusion-weighted MR imaging (DW-MRI) in the body are rapidly evolving. This volume highlights state-of-the-art techniques for performing DW-MRI measurement in the body and addresses important practical issues. Key points are highlighted that will help radiologists and technologists to acquire high-quality images for disease assessment and to adapt the technique to their own clinical practice or research. The major clinical applications of DW-MRI in the body, both oncological and non-oncological, are extensively illustrated, providing readers with a broad insight into the growing uses of the technique. The final section addresses future developments, considering the potential importance of the technique in relation to drug development and the ways in which DW-MRI might be combined with other functional imaging techniques to further improve disease assessment.
Principles and Background -- Principles of Diffusion-Weighted Imaging (DW-MRI) as Applied to Body Imaging -- Techniques and Optimization -- Qualitative and Quantitative Analyses: Image Evaluation and Interpretation -- Non-Oncological Applications in the Body -- MR Neurography: Imaging of the Peripheral Nerves -- Evaluation of Organ Function -- DW-MRI Assessment of Diffuse Liver Disease -- Oncological Applications in the Body -- DW-MRI for Disease Detection -- DW-MRI for Disease Characterization in the Abdomen -- DW-MRI for Disease Characterization in the Pelvis -- DW-MRI Assessment of Cancer Response to Chemoradiation -- DW-MRI Assessment of Treatment Response to Minimally Invasive Therapy -- Evaluation of Lymph Nodes Using DW-MRI -- Evaluation of Malignant Bone Disease Using DW-MRI -- Diffusion-Weighted Whole-Body Imaging with Background Body Signal Suppression (DWIBS) -- Future Developments -- Multifunctional MR Imaging Assessments: A Look into the Future -- The Potential of DW-MRI as an Imaging Biomarker in Clinical Trials.
Keywords: Medicine; Radiology, Medical; Internal medicine; Oncology; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Oncology; Internal Medicine